Hemophagocytic Lymphohistiocytosis in Children: Pathogenesis and Treatment - Ishii, Eiichi (Frontiers in Pediatrics, 2016)
Hemophagocytic lymphohistiocytosis (HLH) is a rare disorder in children, which is characterized by fever and hepatosplenomegaly associated with pancytopenia, hypertriglyceridemia and hypofibrinogenemia. Increased levels of various cytokines and soluble IL-2 receptors are biological markers of HLH. HLH can be classified into two distinct forms; primary and secondary HLH. Familial hemophagocytic lymphohistiocytosis (FHL), one of primary HLHs, is an autosomal recessive disorder typically occurring in infancy and can be classified into five different subtypes (FHL1 to FHL5). In Japan, more than 80% of FHL patients have either PRF1 (FHL2) or UNC13D (FHL3) defect. It is now considered that FHL is a disorder of T-cell function, because activity of NK cells or cytotoxic T lymphocytes for target cells is usually impaired. On the other hand, Epstein-Barr virus-associated HLH (EBV-HLH) is considered a major subtype of secondary HLH. Any genetic background could have a role in the pathogenesis of secondary HLH, because EBV-HLH is thought to be particularly prevalent in Asian countries. For primary HLH, hematopoietic stem cell transplantation is an only accepted curative therapy and cord blood transplantation with reduced-conditioning regimen has been used, with superior outcome. For secondary HLH including EBV-HLH, immune-chemotherapy based on HLH-2004 protocol has been used. In the near future, an entire pathogenesis should be clarified in order to establish less toxic therapies including immunotherapy and gene therapy.